A STUDY ON SRI LANKAN CHILDREN’S CONCEPTION OF SPACE - Mukunthan, Thevarasa (Southeast Asia Early Childhood Journal, 2016)
The present study was conducted mainly to investigate the applicability of children’s conception space presented in Piaget’s Cognitive Development theory to Sri Lankan children. The study attempted to identify whether there were variations in Sri Lankan children’s conception of space according to the sectors i.e. urban, rural and estate, they live in, factors affecting Sri Lankan children’s conception of space. The methodology of the study was quantitative and in nature. Piagetian tests modified to suit the Sri Lankan context and the case study method was used in achieving the objectives of the study. The sample of the study consisted of 75 children selected randomly from primary school children between the ages of 5-10 years from Urban, Rural and Estate sectors in the Kalutara district of the Western Province. Modified Piagetian instruments, Observation schedules and in-depth interview schedules were used as instruments for data collection. The findings of the study indicated children’s conception of space the findings revealed that Piaget’s theory is applicable to Sri Lankan children in relation to haptic perception, projection of shadows of the rectangle but other tasks vary age wise and stage-wise. The results of the performance of Sri Lankan children spatial tasks, the study found that that there were no prominent variations in the performance in all three tasks. But the estate children’s performance is slightly higher than that of other children in a few age ranges.